The Gift of Vilnius University to the Burnt Library of Åbo Academy (1827–1829) - Pacevičius, Arvydas (Bibliotheca Lituana, 2014)
Expanding the research about the old Vilnius University Library launched by L. Vladimirovas, this article discusses the fact (which has never been mentioned in historiography), about a gift to the burnt library of Åbo Academy, which then belonged to the Duchy of Finland, Russian Empire. In support action, which was organised by the supreme government of Russian Empire, lots of scientific, educational and cultural institutions took part; one of them was Vilnius University. Successful research of official documents, preserved in Lithuanian State Historical Archive (one of them The books of gifts to Vilnius University, 1820–1832), and the Activity daybook (1823–1832) of Vilnius University Library, as well as lists of donated books, preserved in the Library of Helsinki National University (Catalogus librorum qui bis extant in Bibliotheca Caesareae Universitatis Vilnensis) and in Vernadsky National Library of Ukraine (Katalog ksiąg dubletowych Biblioteki Uniwesyteckiej Wilenskiej oddanych dla zgorzaley Biblioteki Abowskiej i tamże odeslanych roku 1829 dnia 28 lutego), allowed us to specify chronology of this charity act, discover its effectors in Vilnius, and provide qualitative and quantitative parameters of donated books. It was identified, that the shipment of books delivered from Vilnius no earlier than 1829 February 28, consisted of 1481 volumes, mainly doublet books on different topics, which were deposited to the Helsinki University. Alexander Wictor Bohatkiewicz, a librarian and a bibliographer in Vilnius University Library, played a crucial role in the selection of the books. At present, the best part of the donated books is preserved in the National Library of Helsinki University. Completed research makes a premise to a historical digital reconstruction of the donated collection.